2022
DOI: 10.1177/21582440221117807
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Compliance With the New WHO-Recommended Frequency and Timing of Antenatal Care Contacts and Receiving Quality Antenatal Care in Cameroon

Abstract: The objective of this study was to determine whether adherence to the new WHO recommendations for the frequency and timing of antenatal care (ANC) contacts was associated with receiving quality prenatal care in Cameroon. The 2018 Cameroon Demographic and Health Survey yielded a weighted sample of 5,694 women aged 15 to 49 years for analysis. We found that 8.9% of women had at least eight ANC contacts, with 47.3% of those occurring during the first trimester. Overall, 28.3% (95% CI [26.4, 30.3]) of the women re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Furthermore, starting ANC early provides an opportunity for pregnant women to receive a wide range of health services that are important for improving the well-being of the mother and the unborn baby [ 37 ]. This finding is in agreement with existing literature [ 38 , 39 ]. Similarly, women who made four or more ANC contacts were more likely to receive quality ANC in this study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, starting ANC early provides an opportunity for pregnant women to receive a wide range of health services that are important for improving the well-being of the mother and the unborn baby [ 37 ]. This finding is in agreement with existing literature [ 38 , 39 ]. Similarly, women who made four or more ANC contacts were more likely to receive quality ANC in this study.…”
Section: Discussionsupporting
confidence: 94%
“…For instance, if a pregnant woman’s blood pressure is not checked during the first ANC contact, it is likely to be checked during subsequent contacts unlike a pregnant woman who does not visit health facility regularly. This finding is consistent with studies conducted in other countries [ 26 , 33 , 34 , 39 ]. Therefore, strengthening efforts to promote early ANC initiation and increasing the number of ANC contacts could significantly enhance the quality of ANC received by pregnant women in Malawi.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is a concern that pregnant women in Uganda do not complete all Eight (8) antenatal care contacts or more(7, 8, 16). Previous studies demonstrated that pregnant women don’t complete the 8-ANC visits, and the majority are noncompliant and nonadherence to the 8-ANC visits model(31-33) 5,26 . Unfortunately, scanty studies have assessed the implementation outcome on the acceptability of the 8-ANC visits model in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines also clearly outline the interventions and the contact (s) that pregnant women should receive in order to have a healthy mother and baby. As a result, pregnant women who make fewer than eight contacts before delivery may miss the opportunity to receive some essential ANC interventions that are expected to reduce the risk of ABOs before delivery, as demonstrated by a study in Cameroon [ 38 ]. This, in part, may explain the high risk of ABOs among women who made fewer than the eight contacts in the current study.…”
Section: Discussionmentioning
confidence: 99%